Dividend policy and political uncertainty: Does firm maturity matter? - Idris, Adamu Adamu; Bala, Hussaini; Suleiman, Naziru (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
Previous evidence has shown that numerous factors influence dividend policy, but how political uncertainty affects a firms cash dividend policy remains blurry. This study examines the relationship between cash dividends and political uncertainty in Nigeria. More so, the study analyses whether this relationship prevails on matured and non-matured firms. The study employed ordinary least squares dummy variable (LSDV) approach with robust standard error on a data set of non-financial listed Nigerian firms. The results revealed that political uncertainty strongly influences firms cash dividend, and a matured firm tends to pay greater dividends than non-matured firms (firms with more growth options). Thus, this finding suggests that matured firms pay more dividends during period of political uncertainty. Consequently, the study supported the agency theory and the life cycle theory.